Postmodernism and Education - Vera Helena Gomes Wielewicki (Ilha do Desterro)
How related are postmodernism and education? If we bear in mind the traditional concept of education, with sacralized institutions, like universities, imposing rules to be followed, no easy connection can be made with the postmodern moment. Fragmentation and inconsistency, ideas associated with postmodernism, do not seem to match education. Usher and Edwards are aware of the troublesome task they have settled themselves to.